29 Paired Box 5 (PAX5) Cytoplasmic Immunoreactivity in Rectal Carcinoid Tumors: A Novel Finding With Potential for Diagnostic and Prognostic Utility. (11th January 2018) - Fu, Zhiyan; Zuo, Chunlai; Sheehan, Christine; Lee, Hwajeong
Abstract: Objectives: Nuclear expression of the PAX5 protein is widely utilized as a diagnostic marker for B-cell lymphoid malignancies. However, cytoplasmic PAX5 (cPAX5) expression has not been evaluated. Recently we encountered granular cPAX5 staining in rectal carcinoid (grade 1 neuroendocrine tumor [NET] by 2010 World Health Organization) in the absence of nuclear staining. We investigated the specificity of this pattern for rectal carcinoid tumors by evaluating additional NETs and neuroendocrine carcinomas (NECs) from the gastrointestinal (GI) and pancreatobiliary (PB) tracts, and liver. Methods: Archived pathology materials (2004–2017) from 86 NETs and 40 NECs were reviewed. Representative tumor sections were subject to immunohistochemical stain for PAX5 (Ventana pre-dilute clone SP34, monoclonal) antibody. The extent [focal (<10%), patchy (10%-50%), diffuse (>50%)] and intensity [1+ to 3+] of cPAX5 within the tumor was evaluated. Results: cPAX5 was observed in 94% (17/18) rectal NETs and 14% (2/14) pancreatic NETs. Three of 13 (23%) metastatic NET to the liver also showed cPAX5 staining. The intensity was 2+, except for four cases with 1+ staining. The extent was diffuse, except for three cases with patchy staining. No cPAX5 expression was noted in the remaining NET (small bowel [n = 31], stomach [n = 7], appendix [n = 2], cecum [n = 1]) and NEC (rectum [n = 5], colon [n = 11], gastroesophageal junction/esophagus [n = 9], pancreas and bile duct [n = 7], ampulla [n = 5], stomach [n = 1], duodenum [n = 1], anus [n = 1]). Conclusion: cPAX5 immunoreactivity appears fairly specific for rectal NET, and thus may be utilized as a diagnostic and prognostic marker for this entity. The mechanism of the subcellular localization of PAX5 expression warrants further investigation. Given the predominance of cPAX5 in low-grade NET of the rectum, it may be a result of cross-reactivity between the PAX5 antibody and pancreatic polypeptide in L-cell type NET, which is the most common subtype with indolent behavior in the rectum.